Simulated Effect of Carbon Black on High Speed Laser Transmission Welding of Polypropylene With Low Line Energy - Ali, M. Mahmood; Dave, Foram; Sherlock, Richard; Mcilhagger, Alistair; Tormey, David (Frontiers in Materials, 2021)
Laser welding is an important manufacturing tool for a wide variety of polymer products including consumer goods, automotive components and medical devices. The laser process parameters and polymer properties have a significant impact on weld quality. Due to higher heat density generated by the laser transmission welding (LTW) technique, defining a set of suitable parameters for LTW of thermoplastics and composites can be challenging. In this work the effect of carbon black along other control parameters has been investigated for high speed welding using a laser source of 980 nm wavelength with low line energy. In this work, the finite element method (FEM)-based software COMSOL Multiphysics is used to create a 3D transient thermal model for LTW of isotactic polypropylene (iPP) and its composites with carbon black (CB) of concentrations ranging from 0.5 wt. % to 1.5 wt. %. The design of experiments based on Box-Behnken design (BBD) is used to organize the simulation experiments and mathematical models are developed based on multiple curvilinear regression analysis on the simulation findings. Independent control variables include the laser power, welding speed, beam diameter, and carbon black content in the absorbent polymer. The maximum weld temperature, weld width, and weld depth within the transmissive and absorptive layers are considered as dependent response variables. Furthermore, sensitivity analysis is carried out to investigate the impact of carbon black along with other independent variables on the responses. The welding feasibility check was performed on the basis of melt and degradation temperature of the materials, and weld depths of transmissive and absorptive layers. It has been observed that the composites containing 0.5 wt.% and 1 wt.% of CB can be welded successfully with neat iPP. However, due to a degradation temperature problem, composites having a larger proportion of CB (>1 wt. %) appear to be more difficult to weld.